PENERAPAN METODE CERTAINTY FACTOR UNTUK DIAGNOSA PENYAKIT KULIT PADA KUCING BERBASIS WEB - munaldi, munaldi (AMIK Mitra Gama, 2024)
Most skin diseases that occur in house cats are often underestimated and can become serious if not treated immediately. Therefore, tools and systems are needed that allow us to diagnose skin diseases in cats like doctors. This system is an expert system that solves problems in a way that is usually done by experts. This research aims to develop a web-based system for diagnosing skin diseases in cats using the Certainty Factor method. This method is used to increase the accuracy of diagnosis by considering the level of confidence of each symptom in a possible disease. This system was developed with the aim of providing fast and accurate assistance to cat owners and veterinary practitioners in identifying skin problems faced by cats. The diagnosis process begins with symptom data collection via a user-friendly web interface. Next, the Certainty Factor method is used to calculate the level of certainty regarding each symptom regarding the possibility of a particular skin disease. The system also features a continuously updated knowledge base, utilizing the latest information regarding skin diseases in cats. Diagnostic results are presented clearly and easily understood via a web interface, which includes treatment recommendations and actions that can be taken. The success of the system was evaluated through trials using case studies of common cat skin diseases.